Coupled distributed arithmetic coding - Xi Chen; Taubman, D. S. (2011 18th IEEE International Conference on Image Processing, 2011)
In this paper, we propose a novel scheme of coupled distributed arithmetic coding to overcome the de-synchronization problem caused by causal decoding in existing distributed arithmetic coding system. Simulation results show that decoding performance is significantly improved and longer sequences outperform shorter sequences using this approach.